Wind speed analysis and its implications for Muktagacha, Mymensingh, Bangladesh (Journal of Bangladesh Academy of Sciences, 2025)
With its distinctive geography and varied climatic conditions, Muktagacha in Mymensingh, Bangladesh, is well-suited for wind energy exploration. This study investigates wind speed characteristics and the potential for generating wind power in the area from 2019 to 2023. Utilizing statistical methodologies, the research develops probability density functions through Weibull and Rayleigh distributions for monthly wind data analysis. The Weibull model provides a more precise estimation of power density, validated by higher R² and lower RMSE values. The results offer essential insights into wind energy capabilities in Muktagacha, supporting decision-makers and emphasizing the importance of renewable energy in the region.J. Bangladesh Acad. Sci. 49(1); 123-135: June 2025